Integrated education: a study on the Islamic educational thought of Mohammad Natsir - Ishak, Mohd. Shuhaimi; Solihin, Sohirin Mohammad (IIUM Press, 2015)
This study discusses Mohammad Natsir’s concept of integrated education from the Qur’anic perspective. Natsir was concerned with the need to develop the Muslim ummah in Indonesia through educational approaches. He disagreed with the system of Islamic education as represented within Islamic boarding schools known as pesantren, arguing that graduates from such institutions were not equipped with worldly knowledge to maintain their survival and contribute to the development of the ummah in the real world. He equally criticized graduates of Western education for being highly motivated by material interests. The purpose of education, according to Natsir, cannot be separated from the mission of life in this world: that is to promote justice and to eradicate evil practices in the community. Natsir disagreed with the division of knowledge into Eastern and the Western, asserting that both realms of knowledge belong to God. The study attempts to discuss the relevance of his educational thought today as a contribution to the concept of Islamization of knowledge.